Effect of various commercial buffers on sperm viability and capacitation. (August 2014) - Andrisani, Alessandra; Donà, Gabriella; Ambrosini, Guido; Bonanni, Guglielmo; Bragadin, Marcantonio; Cosmi, Erich; Clari, Giulio; Armanini, Decio; Bordin, Luciana
Abstract A wide variety of sperm preparation protocols are currently available for assisted conception. They include density gradient separation and washing methods. Both aim at isolating and capacitating as much motile sperm as possible for subsequent oocyte fertilization. The aim of this study was to examine the effects of four commercial sperm washing buffers on sperm viability and capacitation. Semen samples from 48 healthy donors (normal values of sperm count, motility, morphology, and volume) were analyzed. After separation (density gradient 40/80%), sperm were incubated in various buffers then analysed for reactive oxygen species (ROS) production, viability, tyrosine phosphorylation (Tyr-P), cholera toxin B subunit (CTB) labeling, and the acrosome reaction (AR). The buffers affected ROS generation in various ways resulting either in rapid cell degeneration (when the amount of ROS was too high for cell survival) or the inability of the cells to maintain correct functioning (when ROS were too few). Only when the correct ROS generation curve was maintained, suitable membrane reorganization, evidenced by CTB labeling was achieved, leading to the highest percentages of both Tyr-P- and acrosome-reacted-cells. Distinguishing each particular pathological state of the sperm sample would be helpful to select the preferred buffer treatment since both ROS production and membrane reorganization can be significantly altered by commercial buffers.